Mineralogical and Petrographic Characteristics of the Jurassic Kaban Dacite in the Eastern Sakarya Zone (Olur/Erzurum) - Sar, Abdullah; Kürüm, Sevcan (My University, 2022)
The volcanic rocks of the Kaban dacite, which is the subject of the study, are located in the Olur (Erzurum) region of the eastern Sakarya zone. This zone is divided into four tectonic slices as Hopa-Borçka zone, Artvin Yusufeli zone, Olur Tortum zone and Erzurum Kars Ophiolite zone from north to south, east of the Eastern pontides, and the investigated rocks are located within the Olur-Tortum zone. These rocks are represented by dacites and rhyolites in the study area. Petrographically, it is observed in fine grained grayish, greenish, earthy colors. The main mineral contents are plagioclase, quartz and K-feldspars. Plagioclase, quartz and K-feldspars occur as phenocrysts, but are also observed in microlithic pastes. Plagioclases are characteristic with albite and polysynthetic twinning. Quartz is in the form of anhedral crystals and is distinguished from K-feldspars by its transparent colors in a single nicol.
Keywords: Erzurum; Mineralogy; Petrograpy; Kaban dacite; Olur